Duality for a class of second order symmetric nondifferentiable fractional variational problems - Prasad, Ashish Kumar; Singh, Anant Pratap; Khatri, Sony (Yugoslav Journal of Operations Research; Vol 30 No 2 (2020), 2020)
The present work frames a pair of symmetric dual problems for second order nondifferentiable fractional variational problems with cone constraints and investigate weak, strong and converse duality theorems in the light of second order $\mathcal{F}$-convexity. Suitable numerical examples were constructed in order to validate our results.